Investigation into the orientation of free-falling engineering components upon impact with a surface - Lee, Stephen Siang Guan (2008)
This research was motivated by the lack of understanding of the probabilities of small engineering components, such as those conveyed and oriented by vibratory equipment, coming to rest on their natural aspects or poses. The crux of this research was the design and fabrication of a drop test rig which conforms to the assumptions of the Energy Barrier Method of analysis.